Informal care in different European care systems: Effects of caregiving on mental health over time - Leonie Börner; Ingo W. K. Kolodziej; Jürgen Wasem; Carina Abels (PLoS ONE, 2025)
Background The study explores the impact of informal caregiving on mental health within different European care systems, recognizing the significant role of informal care due to demographic changes and the shortage of formal care options. The growing necessity for informal care is opposed to labor market demands and geographic mobility. A distinction is made between the “family effect” and the “care effect” on mental health, emphasizing the need to explore these impacts across different care systems longitudinally. Methods Utilizing data from the Survey of Health, Aging, and Retirement in Europe (SHARE) across six waves, this study includes respondents aged 30 and older who participated in at least three waves. Participating countries were classified according to support services – outpatient care, payments for nursing care, obligation to support relatives – into the care systems implicit familism, explicit familism and optional familism. We employ least squares dummy variable (LSDV) regression followed by two-stage least squares (TSLS) regression to investigate intra-individual changes and the relationship between informal caregiving and mental health. Results The sample comprises 5,761 individuals, with 2,800 individuals involved in informal caregiving across three defined care systems. LSDV-results show that caregiving significantly affects mental health in explicit familism for both genders and in implicit familism for women, increasing depressive symptoms as measured by the EURO-D score. These findings are not confirmed by TSLS-results. Instead TSLS-results show positive significant influence of informal care on mental health for both genders in implicit familism which include a reduction of EURO-D score and no significant results in explicit familism. Conclusion The study highlights the differential impacts of informal caregiving on mental health across European care systems. The policy frameworks in implicit familism appear to benefit informal caregivers. Future research should further explore the dynamics of care systems and the role of policy interventions in supporting caregivers’ mental health.